Enhancement in room temperature ammonia sensing performance of the La substituted SnO2 (La:SnO2) thin films developed using spray pyrolysis technique. (1st May 2022) - Boomashri, M; Perumal, P; Vinoth, S; Shkir, Mohd; AlFaify, S
Abstract: In this report, pristine SnO2 and La doped SnO2 (La:SnO2 ) thin films were synthesized using the spray pyrolysis technique and their gas sensing performance operated at room temperature in the presence of ammonia (50 to 250 ppm) were analyzed. The La:SnO2 thin films were developed in four different La concentration like 0, 1, 3 & 5% in SnO2 . All the prepared thin film samples were characterized using different analytical techniques for analyzing their properties. The XRD result shows the prepared La:SnO2 (0, 1, 3 & 5%) thin films exhibits a tetragonal rutile structure of SnO2 without any secondary impurities according the JCPDS data (41–1445). Also, the crystallite size increases with the La doping concentration at 1% and decreases with further increase in La concentration (3 & 5%) could due to the deterioration of the grain growth of the Sn-O lattice. The scanning electron microscope (SEM) results shows the La:SnO2 thin films possess a tetragonal structures with different nano size particles and the energy dispersive x-ray analysis (EDX) confirms the presence of Sn, O & La elements. The optical results suggest that the transparency increases with the introduction of the La dopants slightly shifted towards the blue region. The bandgap of the samples increases with the increase in La concentration which is according to the Moss- Burstein effect. The photoluminescence (PL) studies confirms the 1% La:SnO2 thin films has higher defect sites due to the presence of oxygen vacancies. Finally, the gas sensing properties of the samples shows that the 1% La:SnO2 exhibits high response of 128% for 250 ppm of ammonia gas at room temperature. Also, 1% La:SnO2 possess stable current value for the fixed concentration of ammonia (250 ppm) during five cycles. This results suggests that the fabricated 1% La:SnO2 thin film sensor can be better suited for the commercial gas sensing application.